FACTORS WHICH CAUSE OF ANXIETY AND DEPRESSION IN PREGNANT WOMEN THROUGHOUT COVID-19 - Viviana Hamat (Journal of Psychiatry Psychology and Behavioral Research, 2023)
Background: COVID-19 has become a critical general medical condition and is causing unfavorable health outcomes for both mother and child.Objective: To determine the causes of fear and mental stress in pregnant women during the COVID-19.Method: By searching for sources used from PubMed and google scholar. The articles sourced are national and international articles published from 2016 to 2021.Results: During the Covid-19 pandemic, most pregnant women experienced increased fear and mental stress. One research article in Turkey showed that the mean IDAS II score of pregnant women increased from 184.78 ± 49.67 before the pandemic to 202.57 ± 52.90, during the COVID-19 pandemic. Mothers with symptoms of mental distress and anxiety are at risk of abortion and early labor (<39 weeks), as well as postpartum depression.Conclusion: Multiple factors involving of maternal age, low education, work, work, social support, lack of physical activity, economy, fear of COVID-19, gestational age were the cause of anxiety and mental stress in pregnant women during the COVID-19. Keywords: anxiety, depression, pregnant.